The effect of climatic changes on vertical moisture exchange in soils (the Volga river basin as an example) - Sergey A. Lavrov (Водное хозяйство России: проблемы, технологии, управление)
The effect of climatic changes on surface and underground runoff cannot be explained without studying such changes on such processes of moisture transfer in soils as infiltration, evaporation, migration of moisture to the frost front. These processes are components of moisture exchange in soils and almost completely determine the mechanisms of runoff formation and its climatic interconformity. The paper discloses the main links of vertical moisture exchange in soils with environmental factors such as temperature, precipitation, wind speed and water vapor pressure. On the example of the Volga basin, changes in moisture flows in soils over the past decades are considered.